The world of art and archaeology: The ideal place for a chemist? - Gonzales Gil, Patricia (2013)
Although we may think that studies of archaeological and artistic objects are mainly historical or stylistic, a chemical approach can also provide important information about them.  In a country like ours, with a vast cultural heritage, a chemist can do a lot to further our knowledge of these objects and to help in their conservation.